Mengintegrasikan Hukum Pemilu: Harmonisasi Peraturan KPU dengan Putusan Mahkamah Konstitusi dalam Penyelenggaraan Pemilihan Kepala Daerah - Arifin, Firdaus (Universitas Muara Bungo, 2025)
The harmonization between the regulations of the General Elections Commission (KPU) and the Constitutional Court (MK) decisions is crucial in ensuring the implementation of Regional Head Elections (Pilkada) following constitutional principles. However, discrepancies between KPU regulations and MK decisions often create legal uncertainty and threaten the legitimacy of the democratic process. This study aims to analyze the legal challenges and implications of such harmonization, focusing on the conformity of KPU regulations with MK rulings. The research employs a normative juridical method with a descriptive-analytical approach involving analyzing primary and secondary legal materials. The findings reveal that KPU frequently fails to align its regulations with MK decisions, leading to inconsistencies in Pilkada implementation. The implications of these findings include the need for enhanced cooperation between KPU and MK and strengthening KPU's internal capacity in legal interpretation. This study contributes to the development of legal harmonization theory and provides practical recommendations for improving the governance of Pilkada in Indonesia.